BEYOND BALANCED SCORECARD: KINERJA ORGANISASI BERNUANSA RELIGIUSITAS - Hanif Hanif (Jurnal Manajemen, 2021)
This study aims to explore the meaning of comprehensive performance measurement from the perspective of the individual manager of the Health Service Organization X in Jakarta. The research method uses transcendental phenomenology. Researchers visited to the field, to understand the research site, discuss, and conduct interviews. The results of the discussions and interviews were analyzed according to transcendental phenomenology research procedures, namely noema, finding the most surface meaning, then noesis, the deeper meaning part, then doing ephoce (bracketing), intentional analysis, and eidetic reduction to arrive at the discovery of "the essence". The research finding is that it produces the essence of comprehensive performance measurement that goes beyond the balanced scorecard system, which is metaphorized by two tringular pyramid hierarchies, “a small tringular pyramid within a larger tringular”. The smaller tringular pyramid has a peak “humanist profit”, which is formed by three interconnected foundations: organizational commitment, wholehearted service, “family” price. The second layer is the larger tringular pyramid that houses the smaller pyramid which has the peak of "performance religiosity", which is the center of all achievements, where every movement and activity of the organization is in the context of serving The Creator. Keywords : organizational commitment, wholehearted service, “family” price, humanist profit, performance religiosity, fenomenology. References: Adian, Donny Gahral. 2010. Pengantar Fenomenologi. Jakarta : Penerbit Koekoesan Anthony, Robert dan Vijay Govindarajan. 2004. Management Control System. McGraw Hill. Boston. Ashton, Robert H. 1990. Pressure and Performance in Accounting Decision Settings : Paradoxical Effects of Incentives, Feedback, and Justification. Journal of Accounting Research, Vol 28. Burrel, Gibson dan Morgan, Gareth. 1997. Sociological Paradigms and Organizational Analysis, England:Ashgate Publishing Limited Prawironegoro, Darsono. 2010. Filsafat Ilmu. Jakarta: Nusantara Consulting Prawironegoro, Darsono.2012. Fenomenologi Admund Husserl. Makalah PDIA Universitas Brawijaya Malang Hanif, H., Rakhman, A., & Nurkholis, M., Pirzada, Kashan. (2019b). Intellectual capital: extended VAIC model and building of a new HCE concept: the case of Padang Restaurant Indonesia. African Journal of Hospitality, Tourism and Leisure Hansen, Don R, Maryanne M. Mowen. 2005. Management Accounting. South Western. Thomson Hilton, Ronald. 2008. Managerial Accounting. Irwin McGraw-Hill Kamayanti, Ari (2016). Metode Penelitian Kualitatif Akuntansi Pengantar Religius Keilmuan. Yayasan Rumah Peneleh Kaplan, Robert S, Norton, David P. (2014). Balanced Scorecard. Terjemahan Bahasa Indonesia. Erlangga Moleong, Lexy J. 2010. Metodologi Penelitian Kualitatif. Bandung: PT. Remaja Rosdakarya Murphy, Kevin J. 1985. Corporate Performance and Managerial Remuneration: An Emperical Analysis. Journal of Accounting and Economics Mutmainah, Siti, Tri Jatmiko Wahyu Prabowo, dan Surya Raharja. 2010. Konstruksi Sosial Pengukur Kinerja Entitas Bisnis: Studi Kasus Ukm di Kudus. Simposium Nasional Akuntansi (SNA) XIII poerwokerto. Sukoharsono, Eko Ganis. 2010. Metamarfosis Akuntansi Sosial dan Lingkungan: mengkonstruksi Akuntansi Sustainabilitas Berdimensi Spiritualitas. Pidato Pengukuhan Guru Besar di Program Akuntansi FEB UB Malang. Triyuwono, Iwan. 2006. Perspektif, Metodologi, dan Teori Akuntansi Syariah. Jakarta: PT. Rajagrafindo Persada